Adobe Photoshop CS5 on demand - Johnson, Steve, 1961- (Que Pub., 2010)
Need answers quickly? Adobe Photoshop CS5 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Includes Workshops ACE Exam Objectives More than 600 Essential Photoshop CS5 Tasks Inside the Book " Improve productivity with the CS5 interface and templates " Use automatic layer alignment and blending to work with objects " Use live filters to view and modify the results of opening files " Use more precise color correction to enhance a photo " Use content-aware options for scaling and fill " Use image trickery to change or enhance an image " Create eye-catching bevels and special effects " Transform plain text into a show-stopping image " Create and manipulate 3D models using presets and custom options " Use tool presets to construct the right tool for the right job " Test content on different target devices Bonus Online Content Register your book at queondemand.com to gain access to: " Workshops and related files " Keyboard shortcuts